2012
DOI: 10.1111/j.1742-4658.2012.08677.x
|View full text |Cite
|
Sign up to set email alerts
|

The NF‐κB target genes ICAM‐1 and VCAM‐1 are differentially regulated during spontaneous differentiation of Caco‐2 cells

Abstract: Intestinal epithelial differentiation entails the formation of highly specialized cells with specific absorptive, secretory, digestive and immune functions. Cell–cell and cell–microenvironment interactions appear to be crucial in determining the outcome of the differentiation process. Using the Caco‐2 cell line, which undergoes spontaneous re‐differentiation when grown past confluency, we observed a loss of VCAM‐1 (vascular cell adhesion molecule 1) mRNA expression, while ICAM‐1 (intercellular cell adhesion mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 68 publications
0
19
1
Order By: Relevance
“…NF-κB activation involves its release from IκBα and the subsequent translocation from cytoplasm to the nucleus, where it binds to cognate sequences in the promoter region of many targeted genes, including VEGF, uPA, MMP-9, MT1-MMP, ICAM-1 and COX-2. [33][34][35] Therefore, NF-κB DNA binding activity and translocation from cytoplasm to nucleus are hallmark of its activation. In the present study, we demonstrated that CN and OMBC reduced NF-κB DNA binding activity.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB activation involves its release from IκBα and the subsequent translocation from cytoplasm to the nucleus, where it binds to cognate sequences in the promoter region of many targeted genes, including VEGF, uPA, MMP-9, MT1-MMP, ICAM-1 and COX-2. [33][34][35] Therefore, NF-κB DNA binding activity and translocation from cytoplasm to nucleus are hallmark of its activation. In the present study, we demonstrated that CN and OMBC reduced NF-κB DNA binding activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cells grown in parallel cultures were used to determine phenotypic changes at days 0, 5, 10, 20 and 30, post-confluence. Additional measures of differentiation for cells used in this study have been reported elsewhere [15]. To induce dedifferentiation, cells at the 20th day of differentiation were detached and replated at about 50% confluence and RNA and protein were harvested 5 days following replating.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Several important targets of NF-kB-mediated transcription, such as intercellular adhesion molecule 1 (ICAM1), were reported to associate with and be highly expressed in HCC progression. 6,7 Although it was not associated with effects on cell survival, ICAM1 was linked to mediate cell adhesion and extravagation in both tumor progression and metastasis. 6,7 In addition, NF-kB was a key transcription factor in the regulation of the expression levels of matrix metalloproteinases (MMPs), and the activated NF-kB signaling cascade was reported to upregulate MMP2 and MMP9 expression levels in HCC cells.…”
Section: Introductionmentioning
confidence: 97%
“…6,7 Although it was not associated with effects on cell survival, ICAM1 was linked to mediate cell adhesion and extravagation in both tumor progression and metastasis. 6,7 In addition, NF-kB was a key transcription factor in the regulation of the expression levels of matrix metalloproteinases (MMPs), and the activated NF-kB signaling cascade was reported to upregulate MMP2 and MMP9 expression levels in HCC cells. [8][9][10] Therefore, tight regulation and modulation of the NF-kB signaling cascade is necessary in HCC progression and malignancy.…”
Section: Introductionmentioning
confidence: 97%